2016
DOI: 10.1177/2158244016638132
|View full text |Cite
|
Sign up to set email alerts
|

A Stakeholder Approach to Community Participation in a Rural Development Project

Abstract: The present study investigates a rural community project (Nguni Cattle Project) that uses Participatory Rural Appraisal (PRA) as a tool for its operational focus. The main objective of the study is to identify how the stakeholders are reflecting the PRA goal of the project. The method used to categorize the stakeholders is reported. The participatory patterns of the stakeholders are then analyzed, with emphasis on the points of intersections where the stakeholders meet to make sure the beneficiaries are suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…Participation in the workplace is regarded as a marked shift from top-down and individualistic perspective of leadership toward a leadership model that empowers employees to identify with the objectives of their work. From an agricultural extension management perspective, the chief motivation for an agricultural extension leader or manager to implement participation programs is the potential for converging disparate views around common objectives (S. E. Usadolo & Caldwell, 2016). Some agriculture extension theorists have suggested that this is achieved by the replacement of top-down leadership approach by one that is horizontal and supportive to achieve mutual responsibility (Nair & White, 1993;S.…”
Section: Participative Leadershipmentioning
confidence: 99%
“…Participation in the workplace is regarded as a marked shift from top-down and individualistic perspective of leadership toward a leadership model that empowers employees to identify with the objectives of their work. From an agricultural extension management perspective, the chief motivation for an agricultural extension leader or manager to implement participation programs is the potential for converging disparate views around common objectives (S. E. Usadolo & Caldwell, 2016). Some agriculture extension theorists have suggested that this is achieved by the replacement of top-down leadership approach by one that is horizontal and supportive to achieve mutual responsibility (Nair & White, 1993;S.…”
Section: Participative Leadershipmentioning
confidence: 99%
“…Mitchell et al (1997) stated that stakeholders can develop ideas for managing organizations that are considered capable of providing the power of legitimacy and urgency for the public interest. Collaborative relationships are emphasized to promote mutual understanding in a group (Usadolo & Caldwel, 2016) and stakeholders focus on various types of formal mechanisms rather than one type of formal mechanism for binding stakeholders (Ozdemir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Planning construction of the village was a type or model of searchs of the potential and the idea of the development of the village that emphasize of participation of society in the entire process of construction [25]; [26]; [27]; [28]; [29]; [30]; [31]; [32]. This concept was altered by values and spirit "Gotong Royong" (Community self-help/ mutual cooperation) which has going deep into Indonesian culture.…”
Section: Planning Construction Conceptsmentioning
confidence: 99%